MODEL PENINGKATAN POLA KERJA KERAS MELALUI RELIGIOSITY, MOTIVASI INTRINSIK DAN MOTIVASI EKSTRINSIK (Pada PT. Bank Muamalat Indonesia Cabang Kudus) - Ahmed Ainul Fuadie El Hakiem (Jurnal Ekonomi dan Bisnis, 2017)
The purpose of this study is to describe and analyze the effect of religioustic on the pattern of hardwork through the intrinsic motivativation and ekstrinsic motivation. And create a developmentmodel on the pattern of hard work. The population in this study are all Human Resources at MTsAl Khoiriyah 1 in Semarang, with the amount of 32 people by using kuestionaire. The samplingmethod used is the census method that all members of the population became the sample. Theanalytical method used is multiple linear regression. Based on the results of data analysis can beconcluded that religioustic has the possitive and significant influence on intrinsic motivativation,religioustic has the possitive and significant influence on ekstrinsic motivativation, possitive andsignificant effect on religioustic to the pattern of hard work, possitive and significant effect onintrinsic motivation to the pattern of hard work and possitive and the possitive and significanteffect on ekstrinsic motivation to the pattern of hard work. Also based on the direct effect,indirect effect, and total effect shows the pattern of hard work influenced by intrinsic motivationby 73.1%, the pattern of hard work influenced by ekstrinsic motivation by 46.9%, the patternof hard work influenced by religioustic through intrinsic motivation by 43.3% and the pattern ofhard work influenced by religioustic through ekstrinsic motivation by 32.8%Keywords : Religioustic, Intrinsic Motivation, Ekstrinsic Motivation , and Pattern of Hard Work.